Genotypic, phylogenetic and epidemiological characteristics of porcine reproductive and respiratory syndrome virus strains (PRRSV) in Vietnam - Hòa, Lê Thanh; Roan, Đỗ Thị; Khuê, Nguyễn Thị; Hương, Đoàn Thị Thanh; Nga, Nguyễn Thị Bích (Vietnam Journal of Biotechnology, 2018)
Nucleotide sequence of ORF5 encoding the antigenic GP5 for 11 strains collected from different geographic localities in the country during 2008-2011 were obtained. These nucleotide sequences were analyzed for molecular properties (nucleotides and amino acids) to determine genotype, phylogenetic and molecular epidemiological characteristics compared with PRRSV circulating in Vietnam and worldwide. Analysis of nucleotides and deduced amino acids showed that there was very high level of nucleotide identity and amino acid homology (98 – 100%) between the Vietnamese and Chinese PRRSV strains. Phylogenetic analysis based on ORF5 nucleotide sequences revealed two large groups, one derived from the North American lineage of genotype 2, including 11 PRRSV isolates in this study and another of the European lineage of genotype 1. In the genotype 2, further subgroups were found among which there were strains of Asia (Vietnam, China, India), strains of the European/North American origin (Austria, US, Denmark) and a 2012-isolated strain from Canada, in a separate subgroup. Regarding to the epidemiological analysis, our isolates collected during 2008-2011, completely followed the endemic peaks occurred in Viet Nam, such as those in 2007-2008 and in 2010-2011. They all were determined as highly virulent strains due to high homology to the highly virulent strains of China occurred in those periods. We have some conclusions to be made that the outbreaks of highly pathogenic PRRSV in Vietnam were epidemiologically associated with the endemics occurred in China and originated from China